Comparative analysis of extractive and pressure swing distillation for separation of THF-water separation - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Computers & Chemical Engineering, 2017)
In the present work, extractive and pressure-swing distillation methods are analyzed in detail through steady state ASPEN Plus simulations to propose the most economic method for separation of equimolar mixture of THF-Water. Various solvents were evaluated and DMSO was identified as the most appropriate solvent, as it gave minimum Total Annual Cost (TAC) for desired purity. In case of pressure swing distillation, various pressure ranges were explored to achieve minimum TAC. Configurations for extractive and pressure swing distillation with heat integration were also worked out. The optimum designs of extractive and pressure swing distillation with and without heat integration were compared on a common basis of feed conditions and purity constraints. Results indicate that TAC of extractive distillation with heat integration is 5.2% less than that of PSD with partial heat integration. (C) 2017 Elsevier Ltd. All rights reserved.